STUDY OF EPIDEMIOLOGICAL CORRELATES OF TUBERCULOSIS. - Jethani, Sumit; Semwal, Jayanti; Kakkar, Rakesh; Rawat, Jagdish (Indian Journal of Community Health, 2012)
Introduction: Tuberculosis is a disease of poverty affecting mostly young adults in their most productive years. WHO has suggested that the expected effect of improved diagnostic and treatment services may be negated by an increase in the prevalence of risk factors for the progression of latent TB to active disease in segments of the population. The risk factors broadly described may be biomedical, environmental or socioeconomic. The impact of these other determinants on TB epidemiology in India has yet to be fully understood . Methodology: Study was undertaken on all patients in the age group of 18 years and above with history of cough for more than 2 weeks attending DOTS Microscopy centre of HIMS with or without other symptoms suggestive of tuberculosis attending DOTS Microscopy centre for a period of six months i.e. from 1st July to 31st December 2010 were included in study group. Total patients attended the centre were 538. Results: Majority of participants were farmers 159(43.9%) belonging to lower socio-economic status . Out of 362 study subjects maximum i.e. 162 (44.8%) had past history of pulmonary tuberculosis and only 18 (5.0%) subjects had family history of tuberculosis . While majority (45%) had past history of tuberculosis of which 37.1% had sputum positivity. Smoking was found to be most common type of addiction among 207 (57.2%) followed by alcohol i.e. 129 (35.6%) . Conclusion: Epidemiological factors like literacy status, socioeconomic status, previous history of tuberculosis, smoking & BMI play important role in causation of Tuberculosis.